ANALYSIS OF THE INFLUENCE OF LOOSE TERMINATION LEVEL WITH INCREASING TERMINATION TEMPERATURE OF ELECTRICAL EQUIPMENT USING INFRARED THERMOGRAPHY - Pranoto Budi Laksono (Department of Computer Engineering, Universitas Wiralodra, 2022)
The use of electrical energy in the industrial is very important to drive production machines. Machine maintenance is carried out so that the lifetime of the machine becomes longer so that the production process continues. Temperature is one of the most common indicators of the structural health of equipment and components. This means that the main symptoms of damage to machines and equipment can be indicated by increasing the temperature of the equipment. One of the symptoms of an increase in equipment temperature is due to a loose cable termination. The use of infrared thermography to measure the temperature rise due to loose termination is one of the methods in electrical machine maintenance. Previous studies using infrared thermography to measure the temperature rise due to loose termination have been carried out by many researchers, but these studies did not show a correlation between the level of loose termination and the increase in temperature but only stated that the loose termination caused an increase in temperature. This study focuses on finding the relationship between the level of loose termination compared to standard torque and the increase in temperature at the termination point. This is very useful as a quick overview in determining the level of urgency in maintenance activity, that percentage of loose termination of a certain value below the standard will give an increase in temperature of a certain value as well. This study resulted, for the torque setting condition 67% below the standard (loose) the temperature increase at the terminal was 13.4% - 15.6%, for the torque setting condition 33% below the standard temperature increase at the terminal of 12.3% -13.8% which mean that the increase in temperature is directly proportional to the level of slack termination and is also directly proportional to the increase in the motor speed. If the termination torque level is lower and the motor speed is increased, the terminal temperature rise will be drastically rise.